Decision Support System For Achieving Students With Profile Matching Method - Nera Mayana Br Tarigan Br Tarigan; Bosker sinaga (INFOKUM, 2020)
Determination of outstanding students at school is very important to provide suggestions for students at SMK Karya Serdang Lubuk Pakam. However, in determining student achievement, it is necessary to look at several criteria and accurate assessments, to provide maximum results. SMK Karya Serdang Lubuk Pakam in determining outstanding students has not used a system, so it needs a decision support system in determining outstanding students. The method used in determining outstanding students is the Profile Matching Method. The variables determined in this study are 1) Knowledge. 2) Personality. 3) Extracurricular This system is built by applying the web-based Profile Matching method and MySQL as the database. With the application of the Profile Matching method in determining outstanding students at SMK Karya Serdang Lubuk Pakam from the 20 predetermined candidates, the best student is Putri with a score of 2.16.